Management science, logistics, and operations research - Wang, John 1955 (Advances in logistics, operations, and management science (ALOMS) book series, 2014)
This book examines related research in decision, management, and other behavioral sciences in order to exchange and collaborate on information among business, industry, and government, providing innovative theories and practices in operations research"--